Photobacterium malacitanum sp. nov., and Photobacteriumandalusiense sp. nov., two new bacteria isolated from diseased farmedfish in Southern Spain - Labella Vera, Alejandro Manuel; Castro, Dolores; Manchado, Manuel; Lucena, Teresa; Arahal, David; Borrego, Juan José (Elsevier, 2018)
tThree strains, H01100409BT, H01100413B, and H27100402HT, were isolated from several internal organsof diseased redbanded seabream (Pagrus auriga) reared in Andalusia (Southern Spain). All strains werestudied by phenotypic, including chemotaxonomy, and genomic characteristics. Phylogenetic analysisbased on concatenated sequences of six housekeeping genes (gyrB, ftsZ, topA, mreB, gapA, and 16S rRNA)supported the inclusion of the strains within the clade Phosphoreum of the genus Photobacterium, and twoof the strains (H27100402HTand H01100409BT) formed a tight group separated from the closest speciesP. aquimaris. Genomic analyses, including average nucleotide identity (ANIb and ANIm) and DNA–DNAhybridization (DDH), clearly separated strains H27100402HTand H01100409BTfrom the other specieswithin the clade Phosphoreum with values below the thresholds for species delineation. The chemotaxo-nomic features (including FAME analysis and MALDI-TOF-MS) of H27100402HTand H01100409BTstrainsconfirmed their differentiation from the related taxa. The results demonstrated that strain H01100413Bwas classified as P. aquimaris and the strains H27100402HTand H01100409BTrepresented a new specieseach in the genus Photobacterium, for which we propose the names Photobacterium malacitanum sp. nov.,type strain H27100402HT(=CECT 9190T= LMG 29992T), and Photobacterium andalusiense sp. nov., typestrain H01100409BT(=CECT 9192T= LMG 29994T).
Keywords: Peces - Enfermedades bacterianas; Photobacterium malacitanum; Photobacterium andalusiense; ANI; DDH; Genome; Fish pathogen